Huancavelica, diagnosis for a strategy - Cetraro Cardó, César (2007)
The economy and the regional society are developed on a difficult territory and settled in diverse ecological floors. Despite the neglect of public policies, the population in that territory grows, expands its productive activities and gradually provides services. There persists the heart of a nation that is stubborn in its progress and well-being.